Integration and the Competitiveness of Peripheral Industry. - Krugman, P; Venables, A (CEPR, 1990)
This paper analyses economic integration between two economies; one central, with a large local market, and the other peripheral, with a small local market. Each economy has an imperfectly competitive manufacturing sector. Trade liberalization creates a strong incentive for the imperfectly competitive industry to concentrate in the central region, near the large market. This may cause the direction of net trade to be the opposite of that predicted by factor endowments. This effect may be offset by a lower wage in the periphery than in the centre; we find that in the early stages of integration relative wages in the centre and periphery diverge, with convergence occurring only in the later stages.